Strategi Peningkatan Kemampuan Berpikir untuk Meningkatkan Keaktifan Peserta Didik dalam Pembelajaran PAI di Sekolah - Lutfi Abrari; Miranda Endah Laberta; Gusmaneli Gusmaneli (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research aims to increase students' activeness in PAI learning at school by using strategies to increase thinking skills. The strategy for improving thinking abilities is a strategy that relies on developing students' thinking abilities so that they can solve social problems appropriate to their level of development. This research aims to examine in more depth strategies for improving thinking skills so that they can be implemented effectively in PAI learning at school so as to increase student activity and involvement during the learning process. As for collecting data in this writing, we use literature studies or library research by taking sources from journals, books and other scientific works. By using this learning strategy, it is hoped that it can increase students' activeness in the PAI learning process at school.